Training for “Santri, Future Leaders of Islam” at the El-Firdaus Rimba Melintang Rokan Hilir Islamic Boarding School - Akhyar, Yundri; Ningsih, Wirda; Elmirawati, Elmirawati; Asmidaryani, Asmidaryani (Lebah, 2025)
The goal of this Community Service Program (PKM) is to help students at Pesantren El-Firdaus Rimba Melintang, Rokan Hilir, become more capable leaders.  Future Muslim leaders who preserve Islamic principles, tolerance, and honesty are greatly influenced by their leadership. Before the training was conducted, the students at the El-Firdaus Rimba Melintang Rokan Hilir Islamic have Lack of Leadership Skills.  The training program consists of role-playing exercises, group discussions, practical exercises, and theoretical seminars on Islamic leadership.  A pre-test and post-test approach is used in the study to gauge how well the training worked.  The findings show that students' comprehension of Islamic leadership principles has significantly improved (25%), as have their communication abilities (30%), organisational management (30%), decision-making (28%), and teamwork (22%).  Students' increased self-assurance, initiative, and ability to apply leadership concepts in their everyday lives are further supported by observations and interviews.  In order to guarantee that future generations have the abilities and morals needed to make valuable contributions to society, this program acts as a model for incorporating leadership education into Islamic boarding schools. The implementation of this program faces challenges such as limited access to modern resources and leadership training materials, which can hinder student engagement and learning. The modern resources in question include technology and digital devices such as computers, projectors, and a stable internet connection to support access to training materials in an online and interactive format. In addition, access to the latest training materials, such as leadership training modules based on Islamic values, academic books and articles, and instructional videos from inspirational figures, is often limited due to facility and cost constraints. The absence of these resources can restrict students' opportunities to gain a deeper understanding of leadership concepts and apply them in their daily lives.